Understanding repolarization in the intracardiac unipolar electrogram: A long-lasting controversy revisited - Stoks, Job; Bear, Laura R.; Vijgen, Johan; Dendale, Paul; Peeters, Ralf; Volders, Paul G. A.; Cluitmans, Matthijs J. M. (Frontiers in Physiology, 2023)
Background: The optimal way to determine repolarization time (RT) from the intracardiac unipolar electrogram (UEG) has been a topic of debate for decades. RT is typically determined by either the Wyatt method or the ‘alternative method’, which both consider UEG T-wave slope, but differently. Objective: To determine the optimal method to measure RT on the UEG. Methods: Seven pig hearts surrounded by an epicardial sock with 100 electrodes were Langendorff-perfused with selective cannulation of the left anterior descending (LAD) coronary artery and submersed in a torso-shaped tank containing 256 electrodes on the torso surface. Repolarization was prolonged in the non-LAD-regions by infusing dofetilide and shortened in the LAD-region using pinacidil. RT was determined by the Wyatt (tWyatt) and alternative (tAlt) methods, in both invasive (recorded with epicardial electrodes) and in noninvasive UEGs (reconstructed with electrocardiographic imaging). tWyatt and tAlt were compared to local effective refractory period (ERP). Results: With contact mapping, mean absolute error (MAE) of tWyatt and tAlt vs. ERP were 21ms and 71ms, respectively. Positive T-waves typically had an earlier ERP than negative T-waves, in line with theory. tWyatt -but not tAlt- shortened by local infusion of pinacidil. Similar results were found for the noninvasive UEGs (MAE of tWyatt and tAlt vs. ERP were 30ms and 92ms, respectively). Conclusions: The Wyatt method is the most accurate to determine RT from (non)invasive UEGs, based on novel and historical analyses. Using it to determine RT could unify and facilitate repolarization assessment and amplify its role in cardiac electrophysiology.